2014
DOI: 10.1186/2193-1801-3-382
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and enzyme bioprospection of endophytic bacteria associated with plants of Brazilian mangrove ecosystem

Abstract: The mangrove ecosystem is a coastal tropical biome located in the transition zone between land and sea that is characterized by periodic flooding, which confers unique and specific environmental conditions on this biome. In these ecosystems, the vegetation is dominated by a particular group of plant species that provide a unique environment harboring diverse groups of microorganisms, including the endophytic microorganisms that are the focus of this study. Because of their intimate association with plants, end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 41 publications
(52 reference statements)
4
58
0
5
Order By: Relevance
“…A previous study reported the isolation and identification of important enzymes, such as amylase, esterase, cellulose, and protease from endophytes of mangroves (Castro et al, 2014). Further, production of exo-and endoglucanases have been reported in different groups of bacteria isolated from mangrove sediments (Soares Júnior et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported the isolation and identification of important enzymes, such as amylase, esterase, cellulose, and protease from endophytes of mangroves (Castro et al, 2014). Further, production of exo-and endoglucanases have been reported in different groups of bacteria isolated from mangrove sediments (Soares Júnior et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tabao et al (2010) melaporkan 10 isolat bakteri penghasil selulase yang diisolasi dari berbagai lokasi mangrove di Filipina. Thompson et al (2013) juga melaporkan isolat bakteri selulolitik dari mangrove di Brazil, Castro, et al (2014) 478,2 ± 65,2 0 118,9 ± 7,4 SMT 1.7 284,2 ± 46,3 0 66,4 ± 17,2 SMT 2.5 323,5 ± 10,18 0 225,4 ± 3,7 SMT 2.6 285,2 ± 2,97 0 103,1 ± 3,3 SMT 2.7 210,0 ± 0,51 287, 1 ± 25,5 134,9 ± 4,3 SMT 3.5 291,9 ± 3,62 457,1 ± 29,5 121,4 ± 4,7 SMT 3.6 183,6 ± 14,67 333,4 ± 63,6 110,6 ± 1,2 SMT 4.5 470,9 ± 2,34 406,3 ± 3,8 935 ± 6,1 penghasil selulase dan 3 isolat bakteri penghasil amilase dari mangrove di Ratnagairi, India. Chantarasiri (2016) mengidentifikasi Bacillus cereus yang memiliki aktivitas selulase dari mangrove di Thailand.…”
Section: Materi Dan Metode Pengambilan Sampel Sedimenunclassified
“…To determine esterase activity, previously sterilised Tween 80 was added to the sterilised culture medium containing (in g/l) peptone 10, NaCl 5, CaCl·H 2 O 0.1, pH 7.4 to a final concentration of 1% (v/v) to evaluate the bacterial esterase activity. The presence of halos was considered to indicate enzymatic activity (Castro et al 2014). To determine protease activity, we used a culture medium containing skim milk; and the formation of a halo around the colony was considered indicative of proteolytic activity (Castro et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of halos was considered to indicate enzymatic activity (Castro et al 2014). To determine protease activity, we used a culture medium containing skim milk; and the formation of a halo around the colony was considered indicative of proteolytic activity (Castro et al 2014).…”
Section: Methodsmentioning
confidence: 99%